Peningkatan Perilaku Perawat dalam Pelaksanaan Keselamatan Pasien Melalui Program Supervisi Karu di Ruang Rawat Inap Rumah Sakit B Karawang - Suryani, Lilis (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Patient safety is a key indicator of hospital service quality that must be prioritised by healthcare workers. Nurses, as the frontline providers of care, play an important role in ensuring the implementation of patient safety standards. One factor that influences the successful implementation of patient safety is ward supervisor supervision. This study aims to analyse the effect of ward supervisor supervision on the behaviour of nursing staff in implementing patient safety in the inpatient ward of Bayukarta Hospital, Karawang. This study uses a quantitative approach with a descriptive analytical cross-sectional design. A sample of 53 nurses was determined based on the established inclusion criteria. Data were collected using questionnaires and analysed using the chi-square test. The results showed a significant relationship between ward supervisor supervision and nurse behaviour in the implementation of patient safety (p=0.000; OR=27.00). These findings confirm that effective supervision can improve nurses' compliance and responsibility in implementing patient safety standards. Therefore, hospitals need to strengthen the role of ward supervisors through structured, continuous supervision accompanied by evaluation to foster a culture of patient safety and improve the quality of nursing services.